PENGARUH PERSEPSI KEBERMANFAATAN, PERSEPSI KERUMITAN, DAN PERSEPSI KEPUASAN WAJIB PAJAK TERHADAP PENGGUNAAN E-FILING BAGI WAJIB PAJAK ORANG PRIBADI DI KOTA KUDUS - Nuraini, Fitria (Jurnal Bulletin, 2017)
Effect of Perceptions of Effectiveness, Perception of Complexity, and Perceptions of Taxpayers' Satisfaction on the Use of E-Filing for Individual Taxpayers in the Kudus City. Taxes are a very important source of state income. Various kinds of breakthroughs related to the development of technology and information, then the Directorate General of Taxes introduced Electronic System Filing or better known as the e-filing system. Implementation of e-filing system will greatly assist taxpayers in reporting taxes, but in this case several different taxpayer perceptions about this system will affect the use of the system. This study aims to determine how the influence between perceptions of usefulness, perceptions of complexity and user satisfaction perceptions of the use of e-filing, especially for personal taxpayers in the area of the Kudus City. Analysis of data used is multiple regression analysis with the help of SPSS program. The results showed that the perception of usefulness, user satisfaction perceptions affect the use of e-filing. But the perception of complexity does not affect the use of e-filing.